HUBUNGAN ANSIETAS DENGAN SINDROMA DISPEPSIA PADA TENAGA KESEHATAN DI RSU-C BMC PADANG - Rendri Bayu Hansah; Sri Wahyuni; Lismawati R; Lidia Dewi; Ahdanul Dwi Hernanda (Yayasan Nusantara Hasana Berdikari, 2023)
Dyspepsia syndrome is a series of symptoms such as nausea, regurgitate, bloating, feeling full quickly, stomach feeling full, burping, and pain or discomfort in the epigastrium. Dyspepsia syndrome can becaused by many factors including psychological interference such as anxiety. Examination on dyspepsia patient where no organic cause were found can be caused by psychological problems, which, if this is not being drilled appropriately can lead the disease to be recurred. This research to determine the relation of anxiety and dyspepsia syndrome on health worker at RSU-C BMC Padang. The type of research used is analytic with a cross-sectional approach. The affordable population in this study were all health workers at RSU-C BMC Padang pandemic with 60 samples using simple random sampling. Univariate and bivariate data analysis is presented in the form of frequency distribution and percentage and data processing using the computerized Statistic program. The highest degree of anxiety was minimal anxiety with 25 people (41.7%), the most age characteristic was 21-55 years old, namely 58 people (96,7%), the most gender characteristic was female, namely 50 people (83.3%), the most occupation was nurse, namely 49 people (81.7%), total respondent with family history suffered from dyspepsia syndrome namely 46 people (76.7%), there is a relationship between anxiety and dyspepsia syndrome based on chi-square test, the p value was 0.000 and kruskal wallis test with p value of 0.001. The highest degree of anxiety is minimal anxiety, aged 21-55 years old, female, working as a nurse, having the family history with dyspepsia syndrome, and there is a relationship between anxiety and dyspepsia syndrome.